Jual Beli Uang Rusak Perspektif Hukum Bisnis Syariah - Alfaruq, Muhammad; Harun, Hermanto; Fitri Habi, Nuraida (Center for Religious Studies and Social Empowerment Foundation, 2023)
This study aims to analyze the causes of the practice of buying and selling damaged money in the City of Sungaipuh, Jambi Province. This research is qualitative research that is descriptive qualitative in nature. Based on the results of research in the field, a picture is obtained that (1) The causes of the practice of buying and selling damaged currency in Sungaipuh City, Jambi Province include economic factors, family factors, situational factors and cultural factors; (2) The practice of buying and selling damaged currency by the community in Sungaipuh City, Jambi Province, is carried out at half the price or 50% of the nominal value of the damaged currency, there is a price determined unilaterally by the buyer and there are also buyers who do not set a price (negotiation). ; (3) In terms of Islamic economics, the practice of buying and selling damaged currency that occurred in Sungaipuh City, Jambi Province, is not permissible because it is included in the category of usury fadhl. This is because the money exchanged does not match the original nominal amount or there are additions. Penelitian ini bertujuan untuk mengetahui dan menganalisis penyebab terjadinya praktik jual beli uang rusak di Kota Sungai Penuh Provinsi Jambi. Penelitian ini adalah penelitian kualitatif yang bersifat deskriftif kualitatif. Berdasarkan hasil penelitian di lapangan, maka diperoleh suatu gambaran bahwa (1) Penyebab terjadinya praktik jual beli mata uang rusak di Kota Sungai Penuh Provinsi Jambi diantaranya adalah faktor ekonomi, faktor keluarga, faktor situasional dan faktor budaya; (2) Praktik jual beli mata uang rusak yang dilakukan masyarakat di Kota Sungai Penuh Provinsi Jambi ada yang dilakukan dengan setengah harga atau 50% dari nominal uang yang rusak, ada harga ditentukan secara sepihak oleh pembeli dan ada juga pembeli tidak menetapkan harga (negosiasi); (3) Praktik jual beli uang rusak yang terjadi di Kota Sungai Penuh Provinsi Jambi dalam tinjauan hukum bisnis syariah tidak diperbolehkan karena termasuk kategori riba fadhl. Hal tersebut dikarenakan uang yang ditukarkan tidak sesuai nominal aslinya atau terdapat tambahan.